RETRACTED: The timing of oilseed flax sowing in the steppe zone of Western Siberia - Orlov Artem; Rendov Nikolay; Ershov Vasily; Nekrasova Ekaterina; Mozyleva Svetlana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001